2018
DOI: 10.1039/c8tc05180a
|View full text |Cite
|
Sign up to set email alerts
|

An ultrahigh discharged energy density achieved in an inhomogeneous PVDF dielectric composite filled with 2D MXene nanosheets via interface engineering

Abstract: Simultaneously improved permittivity and breakdown strength, accompanied with reduced dielectric loss and conductivity, are difficult to achieve in polymer nanocomposites with conductive fillers by blending to construct a homogeneous structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 48 publications
2
33
0
Order By: Relevance
“…For instance, An et al [36] realized MXene coatings of stretchable Polydimethylsiloxane that can withstand a large-scale mechanical deformation while maintaining an electrical conductivity as high as 20 S·cm −1 . Feng et al [37] prepared the sandwich Polyvinylidene fluoride (PVDF) composite and demonstrated improved electrical properties. The permittivity of ~26 at 100 Hz, a breakdown strength of ~350 MV·m −1 and AC conductivity 10 −11 S·cm −1 at 100 Hz was reported.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, An et al [36] realized MXene coatings of stretchable Polydimethylsiloxane that can withstand a large-scale mechanical deformation while maintaining an electrical conductivity as high as 20 S·cm −1 . Feng et al [37] prepared the sandwich Polyvinylidene fluoride (PVDF) composite and demonstrated improved electrical properties. The permittivity of ~26 at 100 Hz, a breakdown strength of ~350 MV·m −1 and AC conductivity 10 −11 S·cm −1 at 100 Hz was reported.…”
Section: Introductionmentioning
confidence: 99%
“…Much work has demonstrated that enhanced dielectric constant can be achieved at high filler loading but at the expense of breakdown strength of polymer nanocomposites [23][24][25][26]. Actually, high loading of nanoparticles induces the formation of defects including nonuniform distribution of nanofillers, insufficient interfacial interactions between nanofillers and polymer matrices and occurrence of voids [27][28][29]. The charge separation at interfaces and strong electric field intensification usually lead to clear frequency dependence of dielectric properties and reduced breakdown strength [30][31][32][33].…”
mentioning
confidence: 99%
“…To tackle this challenge, the key is to ensure uniform dispersion of nanofillers and good interfacial compatibility in the polymer nanocomposites at high filler loading [27][28][29][30]37]. Considering the fact that the physiochemical properties of nanofillers and polymer matrices show a great disparity, and large surface-to-volume ratio of nanofillers [38][39][40][41].…”
mentioning
confidence: 99%
“…The Flack parameter of 0.04(5) confirms this fact. 35 Stability Studies in Aqueous Media. Studies in aqueous relevant media of the new bipyridine-based compounds were performed prior to in vitro evaluation in order to access their stability.…”
Section: ■ Results and Discussionmentioning
confidence: 99%